Total Synthesis of Lycoposerramine-R - Watanabe, Shinya; Ishikawa, Masatsugu; Nomura, Toshimune; Fukuyama, Tohru; Yokoshima, Satoshi (Synlett, 2018)
A total synthesis of lycoposerramine-R was accomplished. The synthesis featured a Claisen–Ireland rearrangement to install a two-carbon unit, and a hetero-Diels–Alder reaction to form a cyclic enol ether that reacted with an ethynyl group to construct a cis-hydrindane core containing a quaternary carbon. A 2-pyridone synthesis using 2-(phenylsulfinyl)acetamide was used to complete the synthesis.
Keywords: alkaloids; Diels–Alder reaction; total synthesis; gold catalysis; alkaloids; rearrangement